Effectiveness of digital games in producing environmentally friendly attitudes and behaviors: A mixed methods study. (January 2021) - Janakiraman, Shamila; Watson, Sunnie Lee; Watson, William R.; Newby, Timothy
Abstract: Awareness of environmental sustainability issues alone is not enough. Environmental Sustainability Education (ESE) should produce changes in attitude and encourage lifelong behaviors. However, behavioral changes are curtailed by constraints and negative perceptions, necessitating the use of persuasive pedagogical tools in ESE. Digital game-based learning (DGBL) environments can provide cognitive knowledge, besides emotionally engaging learners by letting them test new behaviors and seeing the consequences instantly. This study examined the effectiveness of DGBL in producing attitudinal and behavioral changes regarding environmental sustainability and about learning experiences from a game, through a mixed methods study. One group of undergraduate students in an educational technology course played EnerCities, an ESE game. Another group played a Science game that was not connected to ESE. The Attitudinal Learning Instrument was administered to collect quantitative data pertaining to attitudinal and behavioral learning after one week and after five weeks of game play. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to develop a model to measure learning. PLS-SEM helps analyze relationships simultaneously in complex models. Quantitative data analysis using PLS-SEM showed that EnerCities was effective in producing attitudinal and behavioral changes that were retained until one week of game play. Thematic analysis of qualitative data, collected through interviews after five weeks of game play, helped interpret why and how attitudinal changes were produced by the game. This provided insights into what game features facilitated cognitive, affective, behavioral and social learning and learning retention, that could be used in future game design. Future research could apply the measurement model to measure long-term retention of attitudinal and behavioral learning using games and other interventions on socio-scientific topics. Highlights: Digital Games help produce environmentally friendly attitudes and behaviors. Cognitive, affective, behavioral and social learning were enhanced because of the game. Study used the Attitudinal Learning Instrument to measure attitudinal learning. PLS-SEM and mixed-methods research provided deep insights into attitudinal learning.